Using REWARD Strategy to Improve Students' Reading Comprehension at SMPN 1 Dringu Probolinggo - Fitriyana Ika Yulianti (Graduate Program, University of Islam Malang, 2021)
REWARD strategy stands for” Read, Watch, Review, and Do”, This strategy is made by the teacher-researcher as the result of the investigation during the home learning as the effects of Covid19 pandemic era at the academic year 2020/2021. This research used class action research with one cycle. The objective of the research was to find out whether the REWARD strategy is effective in improving students’ achievement in reading comprehension through blended learning. The participants of the research were 32 students of the ninth grade students of IX G of SMPN 1 Dringu Probolinggo. In collecting the data, teacher-researcher has collaborated with her colleague to complete the instruments of research, as follows: students’ reading comprehension test, field note, observation checklist, and questionnare. As the learning process of reading comprehension, the activity is divided into three phases; pre-reading, whilst reading, and post-reading that held in Blended Learning Classroom. Those phases are dealed with the REWARD strategy for achieving the best result. Firstly, pre-reading is conducted through reading material by online ( Google Classroom), then whilst reading collaborated by watching video and reviewing the lesson by offline ( Classical Classroom), and postreading phase was done by doing assignments through online ( Google Form).The finding result showed that the use of REWARD strategy was effective. there were 32 students who reached the KKM point (100%) ,but 8 students shows the lower score than the preliminary test, 12 students achieves the same score with the preliminary quiz, 12 students get the higher score than the preliminary quiz. It is added by the participation of students through online and offline classroom. 84 % of students used the activities in meeting one of the process, 86% in meeting two, 88% in meeting three, and 92% in the final meeting. As a result, 87,5% of students used the activities while reading. Based on the research, it is claimed that REWARD strategy is effective in improving students’ achievement in reading comprehension escpecially and more often it can be used by nonenglish teacher in handling blended learning classroom as the need of this digital era.